Experimental Study of Drop Impacts and Spreading on Epicarps: Effect of Fluid Properties - Osorio-Lira, F; Andrade-Pizarro, R (2012)
The fluid mechanic of liquid drop impacts on solid food plays an important role in food engineering, e.g. when a spray technology is used to apply a coating. In the present work, drop impact behavior on banana and purple cabbage epicarps using high speed camera was studied. Drop velocity was controlled by modifying the height from which drop was ejected. Weber number varied from 100 to 800, whereas Reynolds number ranged from 1000 to 12,500. Liquid drop viscosity and surface tension effects on drop impact behavior were evaluated and temporal evolution of both spreading and flattening factors are presented. Results show that viscosity and epicarp surface properties had great influence on impact dynamics. For low viscosity liquid drops (water and Tween 20-water), the maximum spread factor, ? max, scaled with We 0.25±0.02, whereas for viscous fluid (water-glycerol mixture) it scaled with We 0.16±0.02. Finally, a new model was proposed to better fit the experimental data than the Roisman s and Scheller s models. © 2011 Elsevier Ltd. All rights reserved.